"Credit Holidays" - Origins and Cost-effectiveness Analysis of Use by Eligible Borrowers Using Selected Examples - Borys, Marcin (Journal of Finance and Financial Law, 2023)
The occurrence of negative phenomena over the past two years: the Covid-19 pandemic, the temporary disruption of supply chains, the war in Ukraine and the energy crisis has affected many aspects of the global economy, including the rise in inflation and interest rates. All borrowers, including more than two million households in Poland repaying home loans, have been affected by these changes - most notably visible in the dynamic increase in lending rates. In order to help borrowers repay the instalments of such loans granted in zloty, the Legislator introduced legislation in July 2022 allowing for the use of „credit holidays”. The purpose of this article is to present the results of a study carried out on the basis of sample home loans - the impact of the introduction of „credit holidays” on the level of loan principal and instalments, assuming that all the money saved from the suspension of instalments is used to overpay the loan.